Iron bioavailability, nutritional and health-promoting properties of extruded sorghum porridge fortified with Baobab fruit, moringa leaves and Bambara groundnut - Duodu, Kwaku Gyebi (University of Pretoria, 2023)
Thesis (PhD (Food Science))--University of Pretoria, 2023.